Clinical Presentation, Long-Term Follow-Up, and Outcomes of 1001 Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy Patients and Family Members. (June 2015) - Groeneweg, Judith A.; Bhonsale, Aditya; James, Cynthia A.; te Riele, Anneline S.; Dooijes, Dennis; Tichnell, Crystal; Murray, Brittney; Wiesfeld, Ans C.P.; Sawant, Abhishek C.; Kassamali, Bina; Atsma, Douwe E.; Volders, Paul G.; et al.
Abstract : Background—: Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is a progressive cardiomyopathy. We aimed to define long-term outcome in a transatlantic cohort of 1001 individuals. Methods and Results—: Clinical and genetic characteristics and follow-up data of ARVD/C index-patients (n=439, fulfilling of 2010 criteria in all) and family members (n=562) were assessed. Mutations were identified in 276 index-patients (63%). Index-patients presented predominantly with sustained ventricular arrhythmias (268; 61%). During a median follow-up of 7 years, 301 of the 416 index-patients presenting alive (72%) experienced sustained ventricular arrhythmias. Sudden cardiac death during follow-up occurred more frequently among index-patients without an implantable cardioverter-defibrillator (10/63, 16% versus 2/335, 0.6%). Overall, cardiac mortality and the need for cardiac transplantation were low (6% and 4%, respectively). Clinical characteristics and outcomes were similar in index-patients with and without mutations, as well as in those with familial and nonfamilial ARVD/C. ARVD/C was diagnosed in 207 family members (37%). Symptoms at first evaluation correlated with disease expression. Family members with mutations were more likely to meet Task Force Criteria for ARVD/C (40% versus 18%), experience sustained ventricular arrhythmias (11% versus 1%), and die from a cardiac cause (2% versus 0%) than family members without mutations. Conclusions—: Long-term outcome was favorable in diagnosed and treated ARVD/C index-patients and family members. Outcome in index-patients was modulated by implantable cardioverter-defibrillator implantation, but not by mutation status and familial background of disease. One third of family members developed ARVD/C. Outcome in family members was determined by symptoms at first evaluation and mutations. Abstract : Supplemental Digital Content is available in the text.